Percutaneous microwave ablation, perfusion, and reconstruction combined with a synthetic bone substitute in symptomatic bone cysts: a minimum of 26 months follow-up - Wenhan Huang; Yuan Yan; Chongquan Huang; Hongyi Liao; Jinpeng Lin; Yu Zhang (International Journal of Hyperthermia)
Purpose The objective was to describe the technique and clinical outcome of microwave thermal ablation (MWA) and perfusion combined with synthetic bone substitutes in treating unicameral bone cysts (UBCs) in adolescents.Materials and Methods A total of 14 consecutive patients were enrolled by percutaneous MWA and saline irrigation combined with synthetic bone substitutes. Clinical follow-up included the assessment of pain, swelling, and functional mobility. Radiological parameters included tumor volume, physis-cyst distance, cortical thickness of the thinnest cortical bone, and the Modified Neer classification system.Results The mean follow-up was 28.9 months (26–52 months). All UBCs were primary, and all patients underwent the MWA, saline perfusion, and reconstruction combined with a synthetic bone substitute session, except for one patient (7.1%) who required a second session. All patients had good clinical results at the final follow-up. Satisfactory cyst healing was achieved in 13 cases according to radiological parameters. Tumor volume decreased from a mean of 49.7 cm3 before surgery treatment to 13.9 cm3 at the final follow-up (p < 0.01). The physis-cyst distance increased from a mean of 3.17–4.83 cm at the final follow-up (p < 0.01). Cortical thickness improved from a mean of 1.1 mm to 2.0 mm at the final follow-up (p < 0.01). According to the proposed radiological criteria, our results were considered successful (Grading I and II) in 13 patients (92.9%) at the final follow-up.Conclusion Percutaneous microwave ablation combined with a bone graft substitute is a minimally invasive, effective, safe, and cost-effective approach to treating primary bone cysts in the limbs of adolescents.